Uma sequência de atividades para abordar conceitos de oxirredução utilizando a estratégia de resolução de problemas - Rocha, Elter Eduardo Bezerra da (2024)
Teaching electrochemistry is very challenging for teachers, given that it is common for many students to consider chemistry difficult to understand due to its abstract nature, especially the knowledge related to redox reactions. In light of this, a search was conducted in literature databases on chemistry teaching, and many studies found investigate and demonstrate the potential of the Problem-Solving (PS) methodology for science teaching. In this context, this master's thesis aims to understand how a Sequence of Activities (SA) using the PS methodological approach can aid the teaching and learning of redox reactions in basic education. To this end, a sequence of activities for teaching concepts related to redox reactions using the PS methodological approach is proposed. The sequence of activities was developed over five stages: 1) identification of prior knowledge, 2) reading a newspaper article, 3) solving exercises, 4) an expository-dialogued class, and 5) application of a problem. The research subjects are third-year high school students from a private school located in Natal/RN. Data collection instruments included participant observation and questionnaires with closed and open questions applied during the activities. For the evaluation, the obtained data were categorized and analyzed qualitatively. The results show that most students were able to adequately use their knowledge of redox reactions to solve the final proposed problem, which related to their life context. Thus, it can be inferred that the employed methodology enabled students to use scientific knowledge to solve problem situations related to their daily lives.